Prevalence and determinants of smoking tobacco and smokeless tobacco use among a nationally representative population-based sample of older adults in India - Supa Pengpid (2022)
This chapter aimed to determine the prevalence and correlates of smoking tobacco and smokeless tobacco use in older adults in India. The cross-sectional sample consisted of 52,393 individuals (≥50 years) from the Longitudinal Ageing Study in India (LASI) Wave 1 in 2017-2018. Results indicate that the prevalence of current tobacco use was 33.0%, 13.7% current smoking tobacco, and 21.0% current smokeless tobacco use. In adjusted logistic regression analysis, male sex, exposure to stressful life events, underweight, vigorous physical activity, lifetime alcohol use and major depressive disorder were positively associated with current tobacco use, while older age (≥80 years), married, higher subjective socioeconomic status, urban residence, spirituality or religiosity, overweight/obesity, hypertension, diabetes, and lung disease were negatively associated with current tobacco use. While current smoking tobacco decreased with age, current smokeless tobacco use did not significantly decrease with age. Having multiple types of discrimination experiences increased the odds of current smoking tobacco but decreased the odds of current smokeless tobacco use. Higher social support (spirituality/religiosity and social engagement) decreased the odds of current smokeless tobacco use. Low or fair self-rated health status was positively associated with current smoking tobacco. One thirds of older adults in India reported current tobacco use. Several risk factors were identified, which can be targeted in public health interventions.